Pengaruh Iklan Politik Terhadap Persepsi Pemilih Kota Medan Tahun 2018 - Akhyar Anshori (Jurnal Interaksi: Jurnal Ilmu Komunikasi, 2018)
Research aims to understand the influence of advertising political to perceptions of of the city of medan 2018 with research methodology quantitative. In the determination of sample, used in this research is  a multistage random sampling. Technique election sample approach in formula taro yamane conducted in decker and usually based on territorial division. The sample of the in research is 100 people. The subject of study it involves the voters who lives in urban village Pangkalan mansyur kecamatan medan johor of the city of medan. The results of this study found that there is a powerful relationship between the influence of advertising political to the attitudes voters. 37,00% of respondents said that the call political good affect on confidence voters. 49,00% of respondents said that the call political impact on confidence voters. And only 14,00 % of respondents said that that the call political has not been affecting the confidence voters. The result of the research also see the relationship excellent correlation between the influence of advertising political of the decision choose candidate couple. 43,00% of respondents said that the call political very influential of the decision choose candidate couple. 41,00% of respondents said political advertising to have an influence of the decision choose the couple and only 16,00% of respondents who said that there had there an effect between political advertising by a decree of the choose the couple . Largely through advertising political outdoor media, selector has basis in determining attitudes and his behavior. Behavior can be addressed voters delivery voting rights and make the choice of candidate couple who is, in this case one of a pair of future governors and vice governors north sumatra years 2018-2023.